Perspectives of Construction Section in Opolskie Voivodship - Zygmunt, Aleksandra; Szewczyk, Mirosława (Regional Barometer. Analyses & Prognoses, 2012)
Section “Construction” includes the complete construction of buildings (division 41), the complete construction of civil engineering works (division 42), as well as specialised construction activities, if carried out only as a part of the construction process (division 43). The main purposes of the study are: (1) the identification of changes in “Construction” which have occurred in the region, (2) the analysis of the section in the Opolskie Voivodship with the use of financial ratios of enterprises, (3) the identification of prospects for the section. The study uses data from the Central Statistic Office and Monitor Polski B. The empirical analysis is based on the location quotient. Moreover, the comparison of the financial situation of analysed enterprises using liquidity and indebtedness ratios was made.